Respuesta :

Answer:

49

Step-by-step explanation:

I think I have read this right!

You let me know if you did not mean to write the following:

[tex]\sum_{k=1}^{7}(1+(k-1)(2)[/tex]

Alright so the lower limit is 1 and the upper limit is 7.

All this means is we are going to use the expression 1+(k-1)(2) and evaluate it for each natural number between k=1 and k=7 and at both k=1 and k=7.

The sigma thing means we add those results.

So let's start.

Evaluating the expression at k=1: 1+(1-1)(2)=1+(0)(2)=1+0=1.

Evaluating the expression at k=2: 1+(2-1)(2)=1+(1)(2)=1+2=3.

Evaluating the expression at k=3: 1+(3-1)(2)=1+(2)(2)=1+4=5.

Evaluating the expression at k=4: 1+(4-1)(2)=1+(3)(2)=1+6=7.

Evaluating the expression at k=5: 1+(5-1)(2)=1+(4)(2)=1+8=9.

Evaluating the expression at k=6: 1+(6-1)(2)=1+(5)(2)=1+10=11.

Evaluating the expression at k=7: 1+(7-1)(2)=1+(6)(2)=1+12=13.

Now for the adding!

1+3+5+7+9+11+13

  4+  12+    20+13

        16+     33

           49